TINJAUAN TERHADAP PEMBAGIAN HARTA BERSAMA AKIBAT PERCERAIAN YANG PERKAWINANNYA DILAKUKAN DI BAWAH TANGAN - Wita Anugrah Gemilang (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTMarriage under the hand known to the public arises after the promulgation of Law Number 1 of 1974 concerning Marriage and the issuance of Government Regulation Number 9 of 1975 as the implementation of Law Number 1 of 1974. In both regulations it is stated that each marriage other than must be performed according to religious provisions must also be noted. For those who are Muslim and are going to divorce but cannot prove the existence of a marriage with a marriage certificate, they can submit an application for marriage (the determination/ratification of marriage) to the Religious Courts as regulated in Article 7 of the Compilation of Islamic Law (KHI).Problems regarding property in marriage generally arise in the event of a divorce. In unregistered marriages, there will be difficulties in sharing shared assets because there is no legal bond between the two. Therefore, in an underhand marriage, good faith from both parties is needed in resolving various problems through a family gathering. Keywords: Marriage, Divorce, Under the Hand